Analysis of Primary Care Computerized Medical Records (CMR) Data With Deep Autoencoders (DAE) - Thomas, Spencer A.; Smith, Nadia A.; Livina, Valerie; Yonova, Ivelina; Webb, Rebecca; de Lusignan, Simon (Frontiers in Applied Mathematics and Statistics, 2019)
The use of deep learning is becoming increasingly important in the analysis of medical data for applications such as pattern recognition for classification. The use of primary healthcare computational medical records (CMR) data is vital in prediction of infection prevalence across a population and decision making at a national scale. However, to date, the application of machine learning algorithms to CMR data remains under-utilised despite the potential impact for use in diagnostics or prevention of epidemics such as outbreaks of influenza. A particular challenge in epidemiology is how to differentiate incident cases from those that are follow-ups for the same condition. Furthermore, the CMR data are typically heterogeneous, noisy, high dimensional and incomplete making automated analysis difficult. Here we introduce a methodology for converting heterogeneous data such that it is compatible with a deep autoencoder for reduction of CMR data. This approach provides a tool for real time visualisation of these high dimensional data, revealing previously unknown dependencies and clusters. Our unsupervised nonlinear reduction method can be used to identify the features driving the formation of these clusters that can aid decision making in healthcare applications. The results in this work demonstrate that our methods can cluster more than 97.84% of the data (clusters $>$5 points) each of which is uniquely described by three attributes in the data, Clinical System (CMR system), Read Code (as recorded) and Read Term (standardised coding). Further, we propose the use of Shannon Entropy as a means to analyse the dispersion of clusters and the contribution from the underlying attributes to gain further insight from the data. Our results demonstrate that Shannon Entropy is a useful metric for analysing both the low dimensional clusters of CMR data and also the features in the original heterogeneous data. Finally, we find that the entropy of the low dimensional clusters are directly representative of the entropy of the input data (Pearson Correlation = 0.99, R$^2$ = 0.98) and therefore the reduced data from the deep autoencoder is reflective of the original CMR data variability.